Sunshine Trading in an African Stock Market - (:unkn) unknown (My University, 2011)
Purpose - How is liquidity formed in emerging financial markets? Do traders preannounce their orders to attract outside liquidity providers (a practice referred to as sunshine trading)? The purpose of this paper is to study liquidity formation of infrequently traded stocks. It also investigates the role of preopening periods in the formation of liquidity. Design/methodology/approach - The paper focuses on the eight largest stocks traded on the West African Bourse in 2000. The dataset includes all the orders submitted to the market from January 3 to December 13, including their time of placement, limit price, and proposed quantity, and the identity of the broker-dealers who submitted them. The paper analyzes order placement strategies as well as preopening price efficiency and broker-dealers' profits. Findings - The evidence is consistent with broker-dealers engaging in sunshine trading. First, large orders are placed early during the preopening period and are not cancelled. Second, for most of the stocks in our sample, preopening prices reveal information long before trading actually occurs. Third, large volumes are traded without significant price movements. Fourth, the most active brokers' profits are lower than less significant intermediaries' ones, indicating that the former do not manipulate the market. Practical implications - The analysis suggests that the actual liquidity on the West African Bourse is higher than what is indicated by the average state of the order book. This might increase the attractiveness of African stock markets for global portfolio managers. Originality/value - To the best of the authors' knowledge, this paper is the first to empirically study sunshine trading as theoretically analyzed by Admati and Pfleiderer
Keywords: African Research